ANÁLISE DA ADEQUAÇÃO FUNCIONAL E DE DESEMPENHO FÍSICO DE EDIFÍCIO CORPORATIVO PARA FINS DE USO PELO SETOR PÚBLICO, A PARTIR DA AVALIAÇÃO PÓS-OCUPAÇÃO (APO) - Rodrigues, Ana Mafalda; Dias, Camila Pimentel; Gomes, Cristiane de Moraes; Accioli, Marta Elisa Riekstin; Galvão, Thaty Tamara Baldini; Ono, Rosaria; Ornstein, Sheila Walbe (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This research aims at assessing the environmental quality of an office building, based on an application of a set of tools indicated in the methodology of Post-Occupancy Evaluation (POE). As a case study, a building occupied by two Departments of the São Paulo State has been selected. Since 2014 building "Ermírio de Moraes", a former headquarters of a Brazilian very large private company and originally a luxury hotel sited at São Paulo urban center is occupied by offices of the public sector. In this study the main POE methodological procedures such as: data collection and design reading; as built; walkthroughs; checklists, interviews with key people; analysis of technical laws and standards for performance verification; physical performance observation; photographic records; questionnaire to staff and evaluation of the perception of the environment under the users pont of view, were experienced. As a result of the cross analysis, it was possible to propose several improvements and present the main diagnosis and recommendations in systematized maps and graphs.